Knowledge Gaps and Educational Needs on Sexually Transmitted Infections among Public School Students in Paudalho, PE - Pedro Henrique Gomes da Silva; José Sérgio Herculano Gomes da Silva; Elton Santos Guedes de Morais; Anísio Francisco Soares (Archives of Current Research International, 2025)
Adolescence is a transitional phase into adulthood, marked by biological, cognitive, emotional, and social changes that make young people vulnerable to various risk situations, this vulnerability is exacerbated by a lack of adequate sexual education, increasing the risk of sexually transmitted infections (STIs). The aim of this study is to assess students’ knowledge gaps and misconceptions about STIs, among students at a public state school. The research was conducted with students from the Monsenhor Landelino Barreto Lins Reference High School (EREM-MLBL) in the municipality of Paudalho, Pernambuco, Brazil. The inclusion criteria for this study encompassed students who were regularly enrolled at EREM-MLBL and who voluntarily agreed to participate in the evaluative questionnaire. The evaluation questionnaire, created on the Google Forms platform, and administered individually ensuring the privacy of participants’ information was made available after obtaining the Free and Informed Consent Form (TCLE). As a result, a total of 61 students responded to the questionnaire, with 52.5% identifying as male, 45.9% as female, and 1.6% as non-binary. Regarding the results, although students demonstrated knowledge about more common STIs, such as HIV, HPV, and hepatitis, there were significant gaps in their understanding of less well-known infections. Additionally, many students were unaware of the various modes of transmission of these infections. While 90.2% of the students recognized condoms as the safest method for preventing STIs, only 63.3% reported having used a condom during their first sexual encounter. Another notable finding is that, in the case of suspected infection, most students would turn to their parents or guardians, but few felt comfortable discussing sexuality openly, reflecting a communication barrier between young people and their families. Thus, there is a need for quantitative and qualitative improvements in interventions in the field of sexual education within both family and school settings. The lack of communication and adequate knowledge about STIs leaves adolescents vulnerable, underscoring the urgency of educational actions that provide clear and accurate information about sexual and reproductive health.